A Two Stage Approach to Spatiotemporal Analysis with Strong and Weak Cross-Sectional Dependence - Natalia Bailey; Sean Holly; M. Hashem Pesaran (Center for Economic Studies and ifo Institute (CESifo), 2014)
An understanding of the spatial dimension of economic and social activity requires methods that can separate out the relationship between spatial units that is due to the effect of common factors from that which is purely spatial even in an abstract sense. The same applies to the empirical analysis of networks in general. We are able to distinguish between cross-sectional strong dependence and weak dependence. Strong dependence in turn suggests that there are common factors. We use cross unit averages to extract common factors and contrast this to a principal components approach widely used in the literature. We then use a multiple testing procedure to determine significant bilateral correlations (signifying connections) between spatial units and compare this to an approach that just uses distance to determine units that are neighbours. We apply these methods to real house price changes at the level of Metropolitan Statistical Areas in the USA, and estimate a heterogeneous spatiotemporal model for the de-factored real house price changes and obtain significant evidence of spatial connections, both positive and negative.
Keywords: C21; C23; 330; spatial and factor dependence; spatiotemporal models; house price changes